ДІДЖИТАЛІЗАЦІЯ В ОСВІТІ: СЬОГОДЕННЯ ТА ПЕРСПЕКТИВИ - Федчишин, Н. О.; Шульгай, А.-М. А.; Крицький, Т. І. (Медична освіта, 2022)
One of the challenges of the digitalized society is the teacher’s readiness for the digital transformation of the educational process, the design of an individual learning trajectory and the organization of a modern process of partnership pedagogy between a pupil and a teacher, a student and a teacher, a teacher and parents. Nowadays, information flows are growing at a tremendous speed, technologies for its processing and storage are developing, and real life is becoming more and more “digitized”. So a modern person can listen to the most interesting lectures at universities, communicate with colleagues from an other part of the planet, take part in seminars, forums, conferences. Such changes affect all aspects of social life, create new opportunities for development, and the education system is not an exception. The article analyzes the use of digital technologies in the education system of Ukraine to improve its effective functioning. Successful experience has beensummarized; the problems of digitalization in education have been highlighted as well. The degree of institutional support for stimulating the development of digitization in education is determined. It has also been emphasized the purpose of providing advisory support to pedagogical staff of educational institutions regarding the implementation of digitalization of the educational space as a means of partner interaction in practical training.